(untitled) (Bangladesh Journal of Anatomy, 2014)
Context : The sacrum generally is composed of five vertebrae fused to form a triangular bony mass with four pairs of sacral foramina. The sacrum may contain six vertebrae, by development of an additional sacral element or by incorporation of the fifth lumbar or first coccygeal vertebrae produces five pairs of sacral foramina. Sacralization is entirely undiagnosable without an X-ray examination and rarely present any symptoms. Sacra of six bodies with five pairs of sacral foramina are found frequently in the department of anatomy during routine study of bones. Material and Methods: The present study was performed on 218 (two hundred eighteen) adult human dry sacra of unknown sex. The study samples were distributed into male and female sex groups by discriminant function analysis The study was descriptive type and was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from January 2011 to December 2011. The sacrum was examined to assess the number of its vertebral segments and sacral foramina. Result : A typical sacrum consisting of 5 segments with four pairs of sacral foramina was observed in 78.9 % cases, while sacralisation with five pairs of sacral foramina was seen in 21.10 % of cases. Conclusion: The number of vertebrae in sacrum may be increased by fusion of fifth lumbar vertebra or first coccygeal vertebra producing sacralization. The knowledge of significant number of sacralization is necessary in managing spinal surgery and for diagnostic and therapeutic purpose in low back pain. DOI: http://dx.doi.org/10.3329/bja.v11i2.20670 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 54-57